Age estimation by evaluation of osteophytes in thoracic and lumbar vertebrae using postmortem CT images in a modern Japanese population - Chiba, Fumiko; Inokuchi, Go; Hoshioka, Yumi; Sakuma, Ayaka; Makino, Yohsuke; Torimitsu, Suguru; Yamaguchi, Rutsuko; Saitoh, Hisako; Kono, Mei; Iwase, Hirotaro (International journal of legal medicine, 2022)
Estimation of age at death is important in forensic investigations of unknown remains. There have been several reports on applying the degree of osteophyte formation—an age-related change in the vertebral body—for age estimation; however, this method is not yet established. This study investigated a method for age estimation of modern Japanese individuals using osteophytes measured on CT images. The sample included 250 cadavers (125 males) aged 20–95 years. The degree of osteophyte formation was evaluated as score O (0–5 points), and the degree of fusion of the osteophytes between the upper and lower vertebrae was evaluated as score B (0–2 points). Age estimation equations were developed using regression analyses with seven variables, determined by scores O and B, and the equation with the smallest standard error of estimate (SEE) was obtained when the number of vertebrae with score O ≥ 2 was used as the explanatory variable. Age estimation with SEE of about 10 years was possible even when partial vertebrae with a high degree of osteophyte formation were used, showing its potential for practical application. The cutoff value for age estimation was established using the receiver operating characteristic curve analysis, wherein good results were obtained for all variables (area under the curve ≥ 0.8). The combination of the estimation equation and the cutoff value can narrow the range of age estimates.